Virtual reality gaming: a tool for reducing fear and anxiety in university students - Zhang, Qian; Peng, Anlin; He, Lihua; Li, Xincheng (Frontiers in Psychology, 2025)
ObjectiveThis study aimed to investigate the effects of outdoor experiential training on the mental health of college students, specifically focusing on anxiety and fear, through the use of virtual reality (VR) technology.MethodsA total of 104 undergraduate participants (20 males and 35 females in both experimental and control groups) were recruited from our university. Participants, aged 18 to 23, were randomly assigned to an experimental group (n = 52) that utilized VR technology for emotional regulation training and a control group (n = 52) that underwent traditional relaxation training. All participants had good mental health status and provided written informed consent. The training lasted for 6 months, with 60-min sessions twice a week. Emotional states were assessed using the SCL-90 scale at baseline, mid-intervention, and post-intervention to evaluate the differences between groups.ResultsStatistical analyses using SPSS 25.0 revealed significant reductions in anxiety and fear symptoms among participants in the experimental group compared to the control group. Specifically, anxiety scores decreased from an average rank of 5.36 to 4.59, and fear scores from 4.60 to 3.78 across the intervention phases. The total SCL-90 scores showed a significant improvement, decreasing from 6.39 to 5.41 (p < 0.05). These improvements were most pronounced during the second phase of the intervention, suggesting that repeated exposure to VR scenarios enhances emotional regulation and psychological resilience.ConclusionThe findings strongly indicate that VR technology is effective in alleviating anxiety and fear among college students, suggesting its potential as a viable intervention tool for mental health improvement in educational settings. The immersive nature of VR provides a safe and controlled environment for students to confront and manage their fears, which can be particularly beneficial for those who are reluctant to seek face-to-face counseling.